Phenotypic plasticity of lippia alba and lippia origanoides (vervenaceae) in response to availability of light (2007)
The distribution of the plant species is usually related to the magnitude of the phenotypic plasticity (PF). With the purpose of to stablish the possible relationship between the magnitude of the PF and the ecological breadth in response to light availability, the PF during the ontogeny in clones of Lippia alba and Lippia origanoides was evaluated. Both species are congeneris and show differences in their distribution. Three random treatments of light availability were set up, low (33%), medium (53%), and high (100%). The PF of morphologic and biomass allocation traits was evaluated during the ontogeny in clones of L. alba and L. origanoides through the ANOVA and the interspecific comparison were carried out through relative distance plasticity index (RDPI). L. alba and L. origanoides displayed variation of the plasticity through the ontogeny in several of the studied traits. The interspecific comparison through RDPI showed that the PF greather of L. alba in comparison to L. origanoides in some state of the ontogeny was not consistent nor uniform. These results suggest a lack association between the magnitudes of the PF in response to the availability of light. Additionally this indicate that the greater distribution of L. alba could be cause by a greater performance in the relative rate of growth and the greater accumulation of total biomass, therefore, it would likely contribute L. alba to reach its sexual maturity faster and the colonization of new areas.